Polimorfismo da nucleoproteína do vírus da raiva de amostras isoladas no Estado do Rio de Janeiro (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
Rabies virus belongs to genus Lyssavirus of the family Rhabdoviridae. The viral nucleoprotein is responsible for several functions in viral particle such as, packing and protects the RNA genome, and participates of transcription and replication of genome. Rabies cause large loss in livestock industry from Rio de Janeiro State, Brazil. All regions of the State are affected by rabies virus transmitted by vampire bat. This work aims to evaluate the changes between the sequences of the nucleoprotein of rabies virus isolated in Rio de JaneiroState. The nucleoprotein gene of 32 samples was sequenced. The sequences length were 1,301 nucleotide, that encoding 433 amino acids. These sequences were aligned with reference sequence Pasteur virus fixed strain (PV GenBank accession number M13215), using ClustalW method. The nucleotide and amino acid polymorphism were analyzed manually using the BioEdit software. Among the samples of herbivores were showed 95 (7.30%) positions with mutation of nucleotides. When comparing the 32 samples of herbivores with PV (GenBank M13215), we observed that there were 257 (19.75%) positions with mutation. Replacements of the transition type were more frequent than the transversion type. Mutations in third nucleotide of the codon were more frequent than in first and second nucleotide. Among the sequences of amino acid from herbivores were showed 13 positions of amino acid substitution. It was observed an increase of 21 replacement of amino acid when the herbivores sequences were compared with PV, totalizing 34 amino acid mutations. The samples of rabies virus show high polymorphism of its nucleotides, but at the level of amino acid the polymorphism is low and even when there are changes in many cases amino acid replacement occurs by the same biochemical amino acid group. Thus the mutations found among the samples have little difference in functionality of the protein, but the nucleotide mutations can be used in rabies epidemiological studies.